THE RETENTION OF COLLEGE STUDENTS MEMBERSHIP BASED ON RELIABILITY AND TANGIBLES OF SERVICE QUALITY ON FITNESS CENTER IN MANADO - Mailoa, Willem; Lapian, Joyce S. L. H. V.; Tumewu, Ferdinand J. (Universitas Sam Ratulangi, 2014)
The reasons why fitness is important for college students are to keep in shape and exercising, but for college students it can be an especially important part of their college years and their overall health, this research is to explore the effect of two important variables that according to author gives significant effect on retention of college students membership in fitness center Manado, the two variables are: reliability and tangibles. This research is tried to prove that the two variables are the most suitable variables to explain the retention on fitness center. Research method that had been used for this research is associated with multiple linear regression analysis technique. The population is college students in Manado, observed based on gender, age, marital status and income rate with sample as many as 100 respondents. The result of this research shows positive impact for these two variables which are reliability and tangibles generally give the significant influence for the customer retentionÂ for college students in Manado. This shows that the quality of service in the fitness center greatly affect a students decision to visit a fitness center. Company must improve their service quality to improve students intention to come in the fitness center. Â Keywords: customer retention, reliability, tangibles